Perampanel effects in the WAG/Rij rat model of epileptogenesis, absence epilepsy, and comorbid depressive‐like behavior. (18th December 2016) - Citraro, Rita; Leo, Antonio; Franco, Valentina; Marchiselli, Roberto; Perucca, Emilio; De Sarro, Giovambattista; Russo, Emilio
Summary: Objective: Perampanel (PER), a selective non‐competitive α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA)‐receptor antagonist, exhibits broad‐spectrum anticonvulsant activity in several seizure models, but its potential disease‐modifying effects have not been investigated. Because of the relevance of AMPA receptors in epileptogenesis and psychiatric comorbidities, we studied the effects of PER in the WAG/Rij rat model of epileptogenesis, absence epilepsy, and depressive‐like comorbidity. Methods: We investigated the effects of acute, subchronic, and chronic treatment with PER (0.25–3 mg/kg) on absence seizures, their development, and related psychiatric/neurologic comorbidity in WAG/Rij rats. Depression‐related behavior was studied by using the forced swimming and the sucrose preference test; anxiety‐related behavior by using the open field and elevated plus maze test; and memory by using the passive avoidance test. Results: PER (3 mg/kg/day orally for 17 weeks starting from P30) significantly reduced the development of absence seizures at 6 months of age (1 month after treatment withdrawal), but this effect was not maintained when reassessed 4 months later. Attenuated absence seizure development was accompanied by reduced depressive‐like behavior in the forced swimming test (FST), whereas no effects were observed on anxiety‐related behavior and memory. Subchronic (1 and 3 mg/kg/day orally for 1 week) and acute PER (0.25–1 mg/kg, i.p.) dosing did not affect established absence seizures and behavior. Significance: These results suggest that AMPA receptors are involved in mechanisms of epileptogenesis in an established model of absence epilepsy, and that these mechanisms differ from those responsible for seizure generation and spread when epilepsy has become established.